Two translations of Mahfouz’s _Awlad Haratina_ (Children of our Alley): A computational-stylistic analysis - Mai Zaki; Emad Mohamed (Journal of Cultural Analytics)
Comparative studies of different translations for the same source text can be valuable sources of insights relevant to the fluid notion of ‘translation style’. Such studies can employ a wide variety of techniques, including computational analysis which targets specific elements in the text in order to allow for a systematic view of translator style. This study attempts a computational-stylistic analysis of the two English translations of Naguib Mahfouz’s controversial novel _Awlad Haratina_ (literally, Children of our Alley). The aim of the study is two-fold. First, it aims to show how quantifiable computational and distant reading techniques can help identify patterns of stylistic differences between these two translations. Second, it attempts to situate the results of this analysis within the wider social context of the two English translations (Stewart 1981 and Theroux 1996) of one of the most famous modern Arabic novels. The results clearly show patterns of linguistic use specific to each of the two translations highlighting differences in lexical variety and richness, sentence structure, readability level, stylometric analysis as well some lexical choices. These results can be interpreted within the social context of producing those two translations, with particular reference to characteristics of retranslation as discussed in the literature.